Curcumin Protects an SH-SY5Y Cell Model of Parkinson’s Disease Against Toxic Injury by Regulating HSP90 - Sang, Qiuling; Liu, Xiaoyang; Wang, Libo; Qi, Ling; Sun, Wenping; Wang, Weiyao; Sun, Yajuan; Zhang, Haina (Cellular physiology and biochemistry, 2018)
Background/Aims: We aimed to explore the protective role of curcumin (Cur) in a cell model of Parkinson’s disease (PD) and its underlying mechanism. Methods: In this study, genes concerned with PD-related keywords were screened within DiGSeE database. The association network between Cur and selected genes was downloaded from STITCH, with the interactions analyzed by STRING. We built a mitochondrial toxin 1-methyl-4-phenylpyridinium (MPP + )-induced SH-SY5Y cell model of PD. Cell morphology was observed under an electron microscope. MTT assay was applied to detect cell proliferation rate. Western blot assay was conducted to determine the level of apoptotic markers, including cleaved caspase 3, Bcl-2-associated X protein (Bax) and B-cell lymphoma-extra-large (Bcl-xl). Tyrosine hydroxylase (TH), dopamine transporter (DAT) protein levels and dopamine (DA) concentration were identified as dopaminergic neuron markers and measured by western blotting or Enzyme-linked immunosorbent assay (ELISA). Results: Cur rescued the toxicity effects of MPP + on SH-SY5Y cells, by controlling morphological change, promoting cell proliferation and inhibiting apoptosis. Of all PD-related genes, HSP90 played an important role in Cur-gene network. HSP90 protein level was elevated by MPP + , whereas Cur could reverse this effect. Silencing of HSP90 significantly attenuated the curative effect introduced by Cur, while HSP90 overexpression enhanced the impact of Cur on PD. Conclusion: Cur can effectively inhibit the toxic effect of MPP + on SH-SY5Y cells and significantly reduce the adverse effects of MPP + on dopaminergic neurons via up-regulation of HSP90.